SHEP1 alleviates cardiac ischemia reperfusion injury via targeting G3BP1 to regulate macrophage infiltration and inflammation - Tingwen Gao; Zhenyang Guo; Xinyu Weng; Yikai Cui; Peng Li; Tao Hu; Wei Luo; Zheng Dong; Peng Wei; Yun Cai; Yijing Lu; Rifeng Gao; et al. (Cell Death and Disease)
Abstract The macrophage-associated inflammation response plays an important role in myocardial ischemia-reperfusion injury (MIRI). SHEP1(SH2 domain-containing Eph receptor-binding protein 1) has been implicated in adhesion and migration of inflammatory cells. However, the role and molecular mechanism of SHEP1 regulating macrophage remains unclear during MIRI. Here, the expression of SHEP1 was increased in macrophages co-cultured with hypoxia-reoxygenated cardiomyocytes and within ischemia-reperfusion injured myocardium at the early stage of injury. Cell migration and inflammation were also enhanced in SHEP1 knock-out macrophages and macrophage-specific deficiency of SHEP1 mice under MIRI, which further led to deteriorated cardiac injury and cardiac function in vivo. Mechanistically, macrophage-derived SHEP1 competitively bound to G3BP1 to suppress inflammation via the MAPK pathway. In addition, administrating inhibitor of G3BP1 could improve cardiac function in macrophage-specific deficiency of SHEP1 mice under MIRI. Our results demonstrate that SHEP1 deficiency in macrophages exacerbates MIRI through G3BP1-dependent signaling pathway. SHEP1-G3BP1 interaction are therefore indispensable for SHEP1 regulated- infiltration and proinflammatory responses of macrophages, which provided a potential and clinically significant therapeutic target for MIRI.